Upaya Membangun Public Trust terhadap Partai Politik di Provinsi Berbasis Syariat Islam Aceh - Alqarni, Wais; Syamsudin, Muhammad Hasan; Saleh, Rahmat (POLITEA, 2023)
One of the public institutions that must provide services by referring to the principles of good governance is a political party. Political parties become part of the state due to state financing through the National Budget (APBN) and Regional Budget (APBD). The purpose of this study is to find out how public trust in local political parties, as well as to find out efforts in building public trust in local parties. The method used is qualitative with a descriptive approach. The result was that local parties must revamp party regeneration if public trust is to increase. In addition, party ideology must be clear so that it is easily understood by the public and also increases public trust in the political party itself. The conclusion from this research is that public trust in political parties is an important thing and one way to achieve this is for parties to be inclusive of the latest issues in their region or region. The next research recommendation that can be carried out is to explore how Islamic law is the basis of the political system in Aceh.